Central Station: Road Movie and Transnational Film - Fardiah Oktariani Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2018)
A certain genre of film generally has certain formulas, that is codes and conventions that is used to represent its elements. In addition, a film could and mostly belong to more than one genre. Road movie generally tells story of people “on the road” or on journey to places, while transnational film can be described as film that is capable to bring about story that can be rooted on any national culture. This study is then attempt to attest Central Station as a road movie as well as a transnational film, which arguably can be done by identifying elements of the film, such as narrative and mode of production, that constitute to a certain genre.Key words : Film, Genre, Road Movie, Transnational Movie, Central Station